Análise da qualidade dos laudos dos peritos contábeis sob a óptica dos magistrados atuantes na justiça trabalhista do Estado do Rio Grande do Sul - Chenet, Hellen Vaccari (2022)
This work aimed to evaluate the quality of the work of experts working in the Labor Court of the state of Rio Grande do Sul. For that, a questionnaire was applied to identify the opinion of the first degree judges of the courts and service centers that fit this requirement. Regarding the methodology, it is a descriptive, quantitative research carried out through a survey with the magistrates. The results show that there are aspects that need improvement, since through the data obtained in the questionnaire, it can be said that the experts lack precision in the reports, indicated by 48% of the magistrates and in clarity with 46% of indications, and in the In the judges' opinion, these are the aspects most in need of improvement. However, the general weighted average of the evaluation of the work of the expert accountants is at acceptable levels, which, compiling all the items described in the NBC TP 01 standard and making the weighted average of the answers, reach 71.9%.